Antimicrobial susceptibility of clinical isolates of Pseudomonas aeruginosa from a Malaysian Hospital - Siva Gowri a/p Pathmanathan; Samat, NA; Mohamed, R (Univ Sains Malaysia, Sch Medical Sciences, 2024)
Indexed by WOS/SCOPUS